Improvement of Home Garden Diversity and Structure by SRFG Program to Support Food Security in Pacitan Regency, Indonesia: SRFG Program to Support Food Security in Pacitan Regency, Indonesia - Wijayanti, Titik; Endang Arisoesilaningsih; Yayuk Yuliati; Amin Setyo Leksono (Journal of Tropical Life Science, 2025)
The research aimed to analyze the contribution of diversity and vegetation structure of the Sustainable Reserve Food Garden (SRFG) Program in Pacitan Regency to support food security. The sampling was carried out using a purposive random sampling on 315 respondents, who were active members of the SRFG Program. Information on the condition of the SRFG home garden was obtained through interviews and questionnaires administered directly to each respondent. The SRFG home gardens were clustered into eight based on vegetation density using multivariate clustering K-Means. Spatial variations in diversity were analyzed using descriptive statistics, density of each vegetation, Shannon-Wiener index diversity, and polynomial model regression analysis using Software PAST 4.13. The research results show that clusters 1-3 had the highest density of trees (302 individuals/ha), of shrubs (11 individuals/ m2), and of herbs (46 individuals/100 m2), with a medium level of diversity (H’ trees 2.09; H’ shrubs 1.91; H’ herbs 1.88). Meanwhile, cluster 2 excelled in herbs density, with the same level of diversity. A low level of diversity (H’ 0.8) was only found in cluster 8 in that of trees. Additionally, the questionnaire results show that the impacts of food availability, food access, food utilization and nutritional health on cluster 1-3 were better than those on cluster 4-8. This is shown on a Likert’s Scale (1-4), where the means of cluster 1-3 were 3.12 in food availability, 3.74 in food access, 3.35 in food utilization and 3.65 in nutritional health. Meanwhile, cluster 4-8 indicated food availability (3.03), food access (3.69), food utilization (3.22) and nutritional health (3.52). The results implies that improving home garden diversity and structure by the SRFG program in Pacitan Regency supports food security.